Elucidation of the epitope of a latency-inducing antibody: identification of a new molecular target for PAI-1 inhibition - Naessens, Dominik; Gils, Ann; Compernolle, Griet; Declerck, Paul J. (Thrombosis and Haemostasis, 2003)
The monoclonal antibody MA-33B8, directed against the serpin plasminogen activator inhibitor-1 (PAI-1), has unique functional properties as it induces acceleration of the active-to-latent transition (Verhamme I et al. J Biol Chem 274: 17511-7, 1999), resulting in PAI-1 activity neutralization. In this study, we have identified Lys88, Asp89, Lys176 and His229 as the major residues of the conformational epitope. Lysine88 and aspartic acid89, contributing the most, are located on the loop between α-helix D and β-strand 2A. Strikingly, these residues undergo dramatic conformational changes during latency conversion. The three-dimensional localization of this epitope and its differential exposure in active and latent forms of PAI-1 provide a molecular explanation for the underlying mechanism of MA-33B8. Rearrangements of hydrogen bonds in this region upon latency transition, strongly suggest that binding of MA-33B8 may result in the generation of energy required in the rate-limiting step of latency transition. Thus, this novel epitope reveals a new interaction site in PAI-1 as a putative molecular target to modulate PAI-1 activity.
Keywords: PAI-1; fibrinolysis; epitope mapping; monoclonal antibody